Quality of life, disease activity and preferences for administration routes in rheumatoid arthritis: a multicentre, prospective, observational study - Direskeneli, Haner; Karadag, Omer; Ates, Askin; Tufan, Abdurrahman; Inanc, Nevsun; Koca, Serdar S.; Gunay, Levent Mert (Oxford Univ Press, 2022)
Objective We aimed to evaluate quality of life (QoL), disease activity, compliance to treatment, patient and physician preferences for route of administration (RoA), status of health and pain in RA patients starting advanced treatments or needing a switch, and the factors associated with patient preferences. Methods A multicentre, prospective, observational and 1-year follow-up study was conducted, between 2015 and 2020, in adult RA patients using advanced treatments for the first time or needing a switch in their current treatments. All the data collected were entered into electronic case report forms. DAS in 28 joints with ESR [DAS28-4(ESR)], EuroQol 5-Dimensional Questionnaire (EQ-5D), HAQ Disability Index (HAQ-DI), Compliance Questionnaire for Rheumatology (CQR-19), Work Productivity and Activity Impairment Instrument (WPAI) and Patient Global Assessment-Visual Analogue Scale (PGA-VAS) questionnaires were used for longitudinal assessments. Results Four hundred and fifty-nine patients were enrolled. Three hundred and eight patients (67.1%) attended the final study visit at 12 months and were included for comparative analyses. Irrespective of RoA, the disease activity and QoL improved significantly at 12 months, whereas compliance worsened. At baseline and 12 months, EQ-5D and DAS28-4(ESR) scores were significantly correlated (P < 0.001). The WPAI scores changed significantly in favour of better outcomes over 12 months after initiation of advanced treatment or switching (P < 0.001). A higher proportion of patients preferred an oral RoA, in comparison to physicians (53.6% vs 31.4%; P < 0.001). Patient and physician RoA preferences were independent of gender, age, disease duration, advanced treatment type and the EQ-5D-3L, DAS28-4(ESR), HAQ-DI, PGA-VAS and CQR-19 scores at baseline. Conclusion The oral route was more frequently preferred by patients compared with physicians, although patients' preference rates showed a slight increase towards the end of the treatment, which might be an important factor for RA outcomes. Better control of disease activity and QoL were achieved at 12 months, regardless of RoA. Lay Summary What does this mean for patients? People with rheumatoid arthritis (RA) and their physicians can have different views throughout the patient journey, whether deciding the main treatment objective, switching a drug or deciding the route of drug administration. However, data are limited in this area. For this purpose, we have conducted a survey study to identify differences between the views of patients and physicians on the management of RA. In this study, we have shown that RA medication compliance decreases over time, irrespective of medication route. This is similar to other studies. We also spotted that there are different routes of drug adminstration (RoA) preferred: a higher proportion of patients preferred an oral RoA compared with physicians (53.6% vs 31.4%, respectively). Patient and physician RoA preferences were not related to gender, age, disease duration, treatment type and disease activity. By surveying patients and physicians at the same time, we have identified their differences better compared with previous studies. Patient preferences should have a major impact on disease management, and the results of this study might encourage patients to discuss their thoughts and preferences with their clinicians to achieve a better outcome.
Keywords: RA; quality of life; patient preference; DAS; ESR; switch; advanced treatment